1978
DOI: 10.1103/physrevlett.40.1391
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Laser-Driven Shock Waves in Aluminum

Abstract: We have observed the structure and velocity of laser-driven shock waves in aluminum foils. We have measured shock velocities as high as IS km/s and shock luminosity risetimes less than 50 ps, and we have inferred pressures of 200 GPa and shock-fvont thicknesses < 0.7 jum. These results suggest that such techniques may be used for measuring equation-of-state parameters and studying the detailed structure of shock fronts.The development of high-power pulsed lasers and high-sensitivity, ultrafast streak cameras h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(24 citation statements)
references
References 3 publications
1
23
0
Order By: Relevance
“…At OMEGA and these other facilities we have implemented variations and additions to the basic arrangement that are not included in the description above. Four of the most useful variations include: (1) schemes to lengthen the duration of the probe pulse; (2) schemes for simultaneous dual wavelength operation, for example at the fundamental (1064 nm) and second harmonic (532 nm) of the probe laser; (3) the addition of an optical recording channel using the existing imaging relay to record thermal luminescence data simultaneous with the VISAR data; and, (4) the addition of dove prisms to enable arbitrary image orientation on the detector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At OMEGA and these other facilities we have implemented variations and additions to the basic arrangement that are not included in the description above. Four of the most useful variations include: (1) schemes to lengthen the duration of the probe pulse; (2) schemes for simultaneous dual wavelength operation, for example at the fundamental (1064 nm) and second harmonic (532 nm) of the probe laser; (3) the addition of an optical recording channel using the existing imaging relay to record thermal luminescence data simultaneous with the VISAR data; and, (4) the addition of dove prisms to enable arbitrary image orientation on the detector.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest laser-driven shock wave experiments studied shock propagation by detecting the thermal luminescence produced when a strong shock breaks through the surface of an opaque stepped target [1,2]. This technique requires the shock to be sufficiently strong that the thermal luminescence is readily detectable after breakout of the shock front; it has been utilized in a number of shock detection studies at high energy laser facilities [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Pressures well below 10 Mbar are currently obtained with traditional laboratory experiments; it appeared that this limit could be extended by using laser-driven shock waves (Veeser et al 1978;Trainor et al 1979). Recently, some short-wavelength laser experiments realized at 0-35 /xm (Yaakobi et al 1981) and at 0-26 urn laser wavelengths have shown the feasibility of easily increasing this range to reach pressures which can only be obtained in the vicinity of nuclear explosions (Ragan III 1980 and; unlike the laser driven shock wave method, this last method has the advantage of achieving the required accuracy necessary to compare, meaningfully, the experimental results and theoretical models of the equation of state of the materials.…”
Section: Introductionmentioning
confidence: 96%
“…These include the measurement of ablation thickness using time resolved X-ray spectroscopy [3], recoil momentum measurements [4], layered target burn trough measurements [2], time resolved X-ray radiography [1], ballistic pendula [9], Faraday cups and plasma energy calorimeters [8], and shock velocity measurements [5,6]. Here we follow the last experimental method, taking advantage of the recent advancement in the generation of high quality shocks and in the measurements of shock velocities with stepped targets [25][26][27].…”
Section: Introductionmentioning
confidence: 99%